Addition of clay based soil ameliorants to light textured soils to reduce nutrient loss and increase crop productivity - Berthelsen, S.; Noble, A.D.; Ruaysoongnern, Sawaeng; Webb, M.; Hengfu, H.; Jiexiang, Y. (2005)
Productivity decline occurs in many agronomic systems due to loss of soil organic matter and a consequent decline in soil fertility. This is pronounced in light textured soils, which even in their pristine state can have low levels of fertility. High temperatures and leaching conditions in tropical environments further exacerbates this poor fertility. In order to facilitate agronomic production on these soils, significant amounts of organic or inorganic fertilizers are required to maintain economic yields. However, the inherent low cation exchange capacity (CEC) of these soils limits their ability to retain nutrients such as Ca2+, Mg2+ and K+. The addition of inorganic fertilizer is often beyond the means of resource poor farmers and has the potential negative impact on the environment due significant leaching losses associated with the high hydraulic conductivity of light textured sandy soils. This paper reviews results from field experiments designed to assess the efficacy of bentonite (high-activity clay with a high CEC) additions on improving crop productivity and reducing nutrient loss. A number of field trials were established on light-textured soils in Northern Australia, Northeast Thailand and Hainan Province in China. Treatments and crop species (including sugarcane and various forage crops) differed at each of the study locations and included a range of rates (from 10 to 60 t ha-1), different application methods (broadcast, banded and slotted), and in some trials a comparison with other commonly used field amendments (e.g. various organic materials and termite mound material). These field trials demonstrated significant increases in crop biomass and yields associated with clay additions. Additional glasshouse studies support the observed increases in biomass observed in the field trials, and suggest that the yield increases were due to a combination of increased water-holding capacity, nutrient availability and reduced nutrient loss. These results support the notion that degraded light textured soils can be highly productive if intrinsic properties are addressed through clay additions.